Sujeitos de direitos com prioridade absoluta? como acontece a gestão e a educação nas instituições de acolhimento públicas para crianças e adolescentes no município de João Pessoa - Guimarães, Larissa Lira (2021)
Host institutions should offer basic food care, hygiene, protection. In addition to these basic care, the host institutions should aim to help children and adolescents to deal with their life history, contributing to them acquiring awareness of themselves, strengthening their identity and building their social place. They should also encourage children and adolescents to perceive themselves as a person with potential, helping them to conquer self-esteem, self-confidence, autonomy and emancipation. In order to achieve these objectives that go beyond mere reception, institutions need to be in line with an educational proposal, which does not develop exclusively in the school environment (formal education), which may happen outside the framework of the official system (non-formal education). Assuming that the development of a non-formal education space in host institutions requires management that has an educational intention and values the role of educator played by the professionals of the institutions, the presente study aims to understand the processo of management and education in public reception institutions for children and adolescents located in the municipality of João Pessoa. It is a qualitative approach, which seeks from exploratory and descriptive data, to understand the social phenomena studied through interaction with the field. The study was conducted in the city of João Pessoa - PB and the data were obtained through semi-structured interviews. Thus, 14 interviews were conducted involving professionals from the host institutions and volunteers from non-governmental organizations and social projects. After data collection, the interviews were fully transcribed from the recordings and the analysis was applied based on the data collected through the narratives. When analyzing the data, it was possible to observe that the professionals of the institutions recognize the educational role they play in the lives of the welcomed, but report that the work overload prevents them from performing their educational functions. Part of the burden reported by educators comes from the various difficulties faced by host institutions in the management of financial resources, human resources and intersectoriality with the network. These issues directly affect under educational processes, making education another one of the rights of children and adolescents that are neglected by the host institutions. Thus, in the results, it was demonstrated that there is no educational intentionality on the part of management or an appreciation of the role of educator played by professionals of the host institutions. Educational processes are perceived in order to fully develop children and adolescents. However, they are not developed by the host institutions that end up relying on the help of ONG’s and social projects to ensure that children and adolescents have an integral education.